Brexit and labour market inequalities: Potential spatial and occupational impacts - Alexander Davenport; Peter Levell (Institute for Fiscal Studies (IFS), 2021)
In this paper we examine the possible distributional impacts of new trade barriers associated with the new Trade and Cooperation Agreement governing relations between the UK and EU after Brexit. We use a model of labour demand that incorporates input-output links across industries, and that allows for demand substitution by firms and consumers and worker reallocation across industries. We find that workers' exposure is moderately increasing across the earnings distribution. Exposure is greater for men than for women as they are more likely to work in manufacturing industries that are relatively harder hit by new trade barriers. Looking across areas, we find that exposure to new Brexit trade barriers is uncorrelated with measures of local deprivation and the impacts of the recent COVID-19 pandemic.
Keywords: D33; D57; F61; F66; J20; 330; Trade; income distribution; inequality